2016
DOI: 10.5424/sjar/2016143-8722
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Survival of honey bees (Apis mellifera) infected with Crithidia mellificae (Langridge and McGhee: ATCC® 30254™) in the presence of Nosema ceranae

Abstract: Crithidia mellificae, a trypanosomatid parasite of Apis mellifera, has been proposed to be one of the pathogens responsible for the serious honey bee colony losses produced worldwide in the last decade, either alone or in association with Nosema ceranae. Since this pathogenic effect contradicts the results of the experimental infections originally performed by Langridge and McGhee nearly 40 years ago, we investigated the potential linkage of this protozoan with colony decline under laboratory conditions. Nosem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
(36 reference statements)
0
13
0
Order By: Relevance
“…This appears to be the case under hive condition as well, since we recovered L. passim-infected honey bees at 37 days after infection. Many parasites share these infection characteristics in order to increase dissemination to other individuals through feces 6,[35][36][37] .…”
Section: Discussionmentioning
confidence: 99%
“…This appears to be the case under hive condition as well, since we recovered L. passim-infected honey bees at 37 days after infection. Many parasites share these infection characteristics in order to increase dissemination to other individuals through feces 6,[35][36][37] .…”
Section: Discussionmentioning
confidence: 99%
“…In the second part of the study, carried out in mid-autumn (2019), the differences in honeybee mortality rates between the L. passim C1 and the ATCC-PRA403 reference strain were determined. To this end, adult worker bees from brood frames kept in an incubator at 34 (±1) °C were caged upon emergence (20 bees/cage; 9 cages) and maintained in incubators (Memmert® IPP500) at 27 °C ( Gómez-Moracho et al, 2020 ; Higes et al, 2016 ). Two days later, the bees were randomly divided into three different treatment groups (3 cages/treatment): L. passim C1 infected bees, ATCC-PRA403 infected bees, and uninfected control bees.…”
Section: Methodsmentioning
confidence: 99%
“…It was suggested that co‐infection by an iridovirus and N. ceranae was linked with honey bee decline in the USA (Bromenshenk et al ., ), but the presence of iridovirus in both CCD and healthy colonies was not lately confirmed (Tokarz et al ., ). A link was suggested between the presence of C. mellificae and N. ceranae in summer, and the negative synergy between the two was proposed to be a predictive marker of winter mortality (Ravoet et al ., ), although laboratory infection with both parasites did not differ from the group infected with N. ceranae only (Higes et al ., ). The combination of certain pesticides and the effects of N. ceranae on bee colonies have also been studied, such as the treatment of sunflowers with the insecticide fipronil and its effect on honey bee colony loss (Bernal et al ., ).…”
Section: Can N Ceranae Kill a Colony?mentioning
confidence: 97%